Improving Financial Literacy Knowledge from An Early Age by Socialization and Training to The Elementary School in Medan City - Rosalia, Vicky; Simatupang, Dewi Ratna Sari; Anggia, Yola (Talenta Publisher, 2022)
Financial literacy is the ability and the knowledge of individual or communities regarding to all their financial resources from decision making until how to manage it. Therefore, education about financial literacy is very necessary from an early age, especially starting from elementary school student. The problem at the 060888 Public Elementary School in Medan at this time is no financial literacy education, so that the correct introduction and implementation of financial literacy has not been implemented yet. By this community service program, students get a good understanding and knowledge about financial literacy. This program is carried out by several methods, there are financial literacy education, implementation of financial literacy, and provide reading corners by providing financial books for elementary school student as well as monitoring and evaluating.